The use of oral thiazoldinediones in correction of hormonal abnormalities among unmarried women with resistant PCO . - Akram, Wisam; Taha, Inas; Saieed, Waffaa N (Journal of the Faculty of Medicine Baghdad, 2007)
Background; Polycystic disease of the• ovary is complex of symptoms with virious clinical, hormonal and biochemical abnormalities. Setting; AL-Elwyia Maternity Teaching Hospital Aim; to test the ability of pioglitazone in correcting biochemical and hormonal changes among unmarried women with PCO. Design; Prospective Methods: 23 women with PCO in whom previous treatment with metformin has failed were recruited to participate in the study. All the women were single with chronic unovulation and menstrual abnormalities and hirsutism. They were put on pioglitazone 30 mg daily for 6 months. FSH, LH, LH/ FSH, fasting insulin level, free testosterone, estradiol, and serum sex binding globulin as well as mid luteal progesterone were assessed prior to treatment and six months later. Results; there was significant reduction in the mean serum fasting insulin level [53.08+12.75 vs. 22.43+4.29: P< 0.001]. In addition there was significant reduction in the mean serum free testosterone, LH and LH/ FSH ratio [3.21+0.36 vs. 1.68+0.43: P<0.001], [15.19+4.43 vs. 10.72+3.08: P<0.001], [2.41+0.23 vs. 1.71+0.12: P<0.001] respectively. In addition mean serum progesterone at mid luteal phase increased significantly [2.44+1.11 vs. 18.61+2.28: P<0.001]. No woman during the treatment course has shown any sign of liver impairment or toxicity. Conclusion; Pioglitazone is an insulin sensitizing drug which may be useful among women with PCO in whom previous treatment with metformin has failed. Yet, caution should be practiced in prescribing the drug until further studies confirm its safety and efficacy.